Trial by television [videorecording] - Gallagher, Paul; Rosenbaum, Steven; Sommers, Cardine (A & E Network [producer], 1993)
Explores both sides of the issue on trial by television by interviewing victims and experts. This investigative report provides stories of actual cases that have been complicated by too much media attention.